NEW APPROACHES TO ENDOCRINOPATHY IN CARDIOVASCULAR DISEASES WITH METABOLIC SYNDROME - Mirzaeva A. Kh. (European Science Publishing, 2025)
Epidemiologic data from observational studies and clinical trials provide substantial evidence of significant overlap between metabolic and cardiovascular diseases. Recognizing this complex relationship, the American Heart Association (AHA) recently introduced the concept of a combined disease known as cardiovascular and metabolic syndrome (CKM), emphasizing the close association and interaction between these areas of health. The purpose of this study is to provide a comprehensive and critical analysis of the current state of play regarding the newly defined CKM syndrome. This includes an examination of the epidemiologic and experimental data establishing links between cardio-metabolic diseases, an exploration of the underlying pathophysiological mechanisms and a comprehensive review of existing treatments.
Keywords: CKM; Cardiovascular metabolic syndrome; Metabolic syndrome; Obesity; American Heart Association (AHA); Hepatoprotector; Gossypol derivative.